EFEKTIVITAS PENGGUNAAN LIDAH BUAYA (ALOEVERA) TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS DIWILAYAH KERJA PUSKEMAS KARANG ANYAR LAMPUNG SELATAN TAHUN 2021 - Maternity, Dainty (Ikatan Bidan Indonesia (IBI), 2022)
Perineal rupture is one of the causes of postpartum maternal bleeding. Postpartum hemorrhage is themain cause of 40% of maternal deaths in Indonesia. One way of natural treatment is by giving aloe vera whichcan accelerate the wound healing process. The purpose of this study was to determine the effectiveness of theuse of aloe vera (Aloevera) on the healing of perineal wounds in postpartum mothers in the Karang Anyar HealthCenter, South Lampung.The Study employed a quantitative research with quasi-experimental approach. The subjects of thisstudy were mothers who experienced perineal rupture of degree I and degree II in the Work Area of the KarangAnyar Health Center, South Lampung, 104 mothers, a sample of 51 data. Data obtained from questionnaires.Analysis using univariate and bivariate analysis using independent t test.The results of this study found that the average value of perineal wound healing given aloe vera(aloevera) was 4.72, standard deviation 1.815. The average value of perineal wound healing that was not givenaloe vera was 7.35, the deviation was 2.545. There is an effectiveness of using aloe vera (Aloevera) on thehealing of perineal wounds in postpartum mothers in the Karang Anyar Health Center, South Lampung(Pvalue=0.026,).Kesimpulan dalam penelitian ini Terdapat efektivitas penggunaan lidah buaya (Aloevera)terhadap penyembuhan luka perineum pada ibu nifas di Wilayah Kerja Puskesmas Karang Anyar LampungSelatan saran penelitian ibu yang mengalami luka perineum untuk merawat luka setalah melahirkan danmengkonsumsi makanan bergizi khususnya makananan yang mengandung protein tinggi agar lukanya cepatsembuh.From the results of the study, researchers suggest mothers who experience perineal wounds to treatwounds after childbirth and consume nutritious foods, especially foods that contain high protein in order toaccelerate the wound healing process